Energy Audit of Three Phase Induction Motor with Capacitor Bank Placement - Garg, Sandeep (My University, 2013)
Rice industry being one of the most energy intensive processes hold a good promise of saving electrical energy. this dissertation through one of its preliminary study of a major rice manufacturing plant Dunar rice industry in Karnal identifies the key areas where electrical energy can possibly be used. induction motor being the major energy consumer in the plant offer oppurtunities of energy saving. in the plant many induction motors are in house wound. this work reports the analysis done on rewound on rewound induction motor for its efficiency.practical comparison between rewound motors and new motors are shown.it is found that rewound motors, if replaced by new ones, have a payback period in the range of 2 years to as less as 6 months. in the second part capacitor placement is done and results are analyzed on energy auditing after power factor improvement by installating capacitor bank to different motors.data analysis has shown that the total capital cost and benefits increased but payback period is decreased as compared to first analysis.
M.E.
Keywords: three phase induction motor; energy audit; capacitor bank; rewound motor